The Influence of E-Wom and Product Quality on iPhone Purchase Decisions among People in Jombang City - David Widianto; Supriyono (Formosa Journal of Multidisciplinary Research, 2024)
IPhone is one of the best products for most people, but in reality the iPhone still gets low reviews from the public. This is partly because the quality of iPhone products is still not good. The purpose of this research is to determine the influence of Electronic Word of Mouth and product quality on iPhone purchasing decisions among people in Jombang City. This research uses primary data obtained from distributing questionnaires and secondary data obtained from literature and the internet. The sampling method used was purposive sampling of 100 respondents. The data analysis method used is Partial Least Square (PLS). The results of this research show that: (1) Electronic Word of Mouth is able to increase iPhone purchasing decisions among people in Jombang City. (2) Product quality can increase iPhone purchasing decisions among people in Jombang City.